Multifunctional hybrid sorption-enhanced membrane reactor - Paulo Ribeirinha (2017)
The growth of the global hydrogen market demands more efficient industrial processes for its production. Hydrogen can be produced from renewable or nuclear sources, using electricity as an intermediate energy carrier. However, industrially is produced mainly by steam reforming of methane or other hydrocarbons and also by gasification of coal and oil refining residues. Methane steam reforming (MSR) is being used for decades, despite the severe operating conditions (high temperatures and pressures) and low-energy efficiency, which challenges the development of more efficient and reliable processes. The present chapter provides an overview of hydrogen production via MSR, purification processes and procedures for enhancing the hydrogen production. Sorption-enhanced and membrane-enhanced reactors, considering selective CO2 sorption removal from the reaction bulk and selective hydrogen membrane permeation are, respectively, addressed. Particular attention was paid to the recently proposed hybrid sorption-enhanced membrane reactor (HSEMR), in which sorption and permeation processes occur inside the reforming reactor. This technology allows lower operating temperatures, produces hydrogen with higher purity and exhibits higher reaction conversions than sorption or membrane reactors. The major contributions in this field are reviewed and the advantages and drawback of each approach are discussed in detail.